Education of Syrian Refugee Children Managing the Crisis in Turkey, Lebanon, and Jordan - Culbertson, Shelly (RAND Corporation, 2015)
With four million Syrian refugees as of September 2015, there is urgent need to develop both short-term and long-term approaches to providing education for the children of this population. This report reviews Syrian refugee education for children in the three neighboring countries with the largest population of refugees-Turkey, Lebanon, and Jordan-and analyzes four areas: access, management, society, and quality.